2013
DOI: 10.5152/akd.2013.180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Gilbert’s syndrome on the dispersions of QT and P-wave dispersion: an observational study

Abstract: Objective: Gilbert's syndrome (GS) decreases the incidence of atherosclerotic heart disease. The aim of the study was to evaluate whether the arrhythmia risk markers such as P-wave dispersion (Pd), QT dispersion (QTd) are reduced in patients with GS compared with healthy subjects. Methods: Sixty-one patients diagnosed with GS (31 females, 30 males) who had applied to the internal medicine outpatient clinic in the hospital were included in this cross-sectional, observational study. A control group of 61 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
0
10
0
5
Order By: Relevance
“…In our study, N1 was found to have a strong correlation with systolic and diastolic BP. HR has been reported to be an independent predictive factor for cardiovascular mortality [24,36]. An increase in HR of 5 beats/minute has been found to increase cardiac mortality by 17%, while the hypertensive subjects with a HR greater than 70 bpm have a threefold higher cardiovascular mortality risk [37].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, N1 was found to have a strong correlation with systolic and diastolic BP. HR has been reported to be an independent predictive factor for cardiovascular mortality [24,36]. An increase in HR of 5 beats/minute has been found to increase cardiac mortality by 17%, while the hypertensive subjects with a HR greater than 70 bpm have a threefold higher cardiovascular mortality risk [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, number of individuals in our study is quite enough for GS illness. Another study reported that level of LDL in GS group was lower than control group, whereas level of HDL in GS group was higher than control group 11 . In the same time that this study resulted similarly with our study, the lipid panel in the GS patients is not evaluated as primer; results are given in order to enforce other findings.…”
Section: Discussionmentioning
confidence: 91%
“…GS diagnosed according to previous studies [10][11][12] . Seventy-two patients diagnosed with GS (38 females, 34 males) who had applied to the internal medical clinic in the hospital were included in this study.…”
Section: Patientsmentioning
confidence: 99%
“…Another study reported that the measurements of P wave and QT interval were found to be lower in GS patients compared to the control group 65 . Both P-wave and QT dispersion are known as the difference between maximum interval and minimum interval by electrocardiography.…”
Section: Gs Reduces the Risk Of Heart Diseasementioning
confidence: 99%
“…P-wave dispersion can be used to determine the risk of atrial fibrillation. Increased QT dispersion can be seen in many patients suffering from cardiac diseases such as patients with left ventricular hypertrophy, patients with heart failure, including idiopathic dilated cardiomyopathy, patients with acute myocardial infarction, hypertensive patients and patients with aortic stenosis 65 . The decreased MPV, P-wave and QT dispersion in GS patients may be related of diminished cardiovascular events.…”
Section: Gs Reduces the Risk Of Heart Diseasementioning
confidence: 99%